2021
DOI: 10.3390/educsci11070317
|View full text |Cite
|
Sign up to set email alerts
|

A Data Science Analysis of Academic Staff Workload Profiles in Spanish Universities: Gender Gap Laid Bare

Abstract: This paper presents a snapshot of the distribution of time that Spanish academic staff spend on different tasks. We carry out a statistical exploratory study by analyzing the responses provided in a survey of 703 Spanish academic staff in order to draw a clear picture of the current situation. This analysis considers many factors, including primarily gender, academic ranks, age, and academic disciplines. The tasks considered are divided into smaller activities, which allows us to discover hidden patterns. Task… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 28 publications
0
8
0
2
Order By: Relevance
“…Ziker et al reported faculty members at a University in the USA worked ~61h per week [ 73 ]. Similarly, a survey conducted in Spain reported that, on an average, faculty work 49h per week (11.5h more than stipulated by law) with 20% of faculty members reporting they worked more than 60 h/week [ 74 ]. The coronavirus pandemic extenuated an already unbalanced workload by increasing stress, burnout, poor mental health and career uncertainty among academics [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ziker et al reported faculty members at a University in the USA worked ~61h per week [ 73 ]. Similarly, a survey conducted in Spain reported that, on an average, faculty work 49h per week (11.5h more than stipulated by law) with 20% of faculty members reporting they worked more than 60 h/week [ 74 ]. The coronavirus pandemic extenuated an already unbalanced workload by increasing stress, burnout, poor mental health and career uncertainty among academics [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that a majority of Lesbian, Gay, Bisexual, Transgender, Queer, and Intersex (LGBTQI+) academics report having experienced discrimination because of their gender identity or sexual orientation (Boustani and Taylor, 2020[308]). A study from Canada reports that while some LGBTQI+ academics have found supportive environments in their department, many have faced sexism, heteronormativity, and cisnormativity (Burchell, Franz-Odendaal and Joy, 2023 [309]). Surveys among LGBTQI+ identified academics in the United States found that publication counts were lower for LGBTQI+ academics who did not disclose their identity.…”
Section: Research and Evidence On The Topicmentioning
confidence: 99%
“…The rapid shift to remote teaching posed numerous difficulties for lecturers, including an increased workload arising from the need to acquire new skills for online instruction and adapt teaching methods to the virtual format (Augustus 2021). As women are more frequently assigned undervalued academic tasks such as teaching, tutoring, and student supervision (Misra et al 2012;Weisshaar 2017;Cabero and Epifanio 2021), they disproportionately experienced work overload during lockdowns.…”
Section: Gendered Impacts Of Covid-19 In Academia: Insights From Prev...mentioning
confidence: 99%